"For Piketty" – a new Enlightenment that goes far beyond rewriting Das Kapital. Issue 2 (8th July 2014) - Jardat, Rémi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This critique of Piketty's Capital in the Twenty-First Century summarizes and comments on the main tenets of the author's principal theory. The author's aim is to point out the book's contributions to a critical debate around social and economic issues, while giving special emphasis to its theoretical and epistemological relevance for management science. Design/methodology/approach – Based on a careful reading of the book, in the original French and English translation versions, the author explores Piketty's arguments and proposals and attempts to place his "scholarly discourse" in relation to Marx's "worldview" as well as the philosophy of the Enlightenment. Findings – The book's potential impact over the long run is extremely high, ostensibly enough to make it as important as Marx's work, but relying on a decidedly different method and philosophy. The author also considers the strong complementariness between this work and that of Pierre Rosanvallon in the field of political science. Some similarities with Fukuyama's approach are also considered, but on a much lesser note. Research limitations/implications – The question of unemployment, which is given little attention in Piketty's work, is not addressed here. Social implications – In contrast with Piketty's book, this paper intends to find social application only within the microcosm of the scholarly community. Originality/value – The author hopes to draw a link between the book's contribution to economic thinking and its philosophical underpinnings, that is by presenting a reading that is both a positivist assessment and an attempt to decipher underlying assumptions.